(3JMQjQ XGgQGJ Gdadc dCbdjOSs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3GbdjOSs ((3YHO GdcGai Hf YHO GdeLjO Hf YHjO Gddg s)
(3ChdgG (B:s
(3HYO GdOjHGLI dCf GdKhGHJ JWdY OGFekG ehGVY HCYjGfgG hJZQH ai ehGVY HCYjGfgG s
(3BNQgG (B:s
(3Ci bhS cGfJ ZjQgG ef Pdc GdfUa fUa GdcQg GdXGgQg hGdHQgGf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B120 - (3U(B126s
(3ajgG HYV GdQShe GdgfOSjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B14 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs